The Relationship Between Knowledge and Attitudes and Waste Management Behavior at SMPN 31 Medan - Aisyah, Siti Nur; Nanda, Meutia; Munthe, Ni’matul Ulya; Muharani, Annisa; Pohan, Rahmaidah (Universitas Ibn Khaldun Bogor, 2024)
Introduction: Indonesia does not yet have an appropriate waste processing system to deal with the increasing amount of various types of waste, and awareness regarding waste processing has become an important topic in the academic environment, especially among students. Objective: This study aims to determine the relationship between knowledge and attitudes and solid waste processing behavior in students at SMPN 31 Medan. Method: This research uses quantitative descriptive methods to describe and analyze certain characteristics with a student population of 459 and a sample of 82 students. Results: The research results show a significant relationship between students' knowledge and behavior towards waste processing with a p-value of 0.014, and there is a significant relationship between students' attitudes and student behavior towards waste processing with a p-value of 0.018. Conclusion: from the results above, it is concluded that knowledge and attitudes play an important role in waste processing behavior at SMPN 31 Medan. Good knowledge about waste processing can influence human behavior in disposing of waste, while a positive attitude towards waste sorting is also related to good behavior in sorting waste. Suggestion: It is hoped that all teaching staff will increase supervision, and students are also expected to comply with applicable rules and regulations and display a good attitude towards the environment.